Accounting Information Systems Genetic Algorithms for All-Optical Shared Fiber-Delay-Line Packet Switches - Liew, S.Y.; Wong, E.S.K. (Canadian Center of Science and Education (CCSE), 2009)
All-optical shared fiber-delay-line (FDL) packet switches have been studied intensively in the literature and with the literature, many scheduling genetic algorithms have been proposed. However, these genetic algorithms suffer from not being able to provide a delay bound, or require complex timing methods to compute scheduling assignments. In this paper, we propose two fast scheduling algorithms for all-optical shared-FDL packet switches. In the first algorithm, packet scheduling is formulated as a tree-searching problem. This is accomplished by breaking down the search tree into multiple smaller subsets and assigning each subset to a parallel processor. By using this method, scheduling solutions can be obtained in a shorter time. Although this approach is superior to other algorithms, its overall complexity and processing overheads are still too high to warrant its day to day use. In the second algorithm, the search tree is carefully trimmed down in order to reduce complexity and overheads. The conclusion will consider a 32 × 32 switch with 32 FDLs, and assume a processor clock rate of 200MHz for schedulers. With this new and second algorithm, a scheduling assignment can be calculated for a given packet in 30ns if 8 parallel processors are employed and we show by simulation that both algorithms can achieve a loss rate of ? 10?7 even at load 0.9, where the average delay is 11.5 timeslots.